Calculation methods of high temperature distribution within structural components and application of these methods to fire resistance assessment: /Aukštų temperatūrų pasiskirstymo statybinėse konstrukcijose skaičiavimo būdai ir jų taikymo analizė įvertinant atitvarų atsparumą ugniai - Mačiulaitis, Romualdas; Lukošius, Kęstutis (Journal of Civil Engineering and Management, 2001)
Fire resistance of a building structure is one of important properties which describes the behaviour of the structure exposed to fire. Performance based on codes allows to use calculation methods. Given a satisfactory characterisation of the heat exposure, the designer may then compute how quickly temperatures will increase at various sections within the structural component. There are many calculation methods. They can divided into three groups (Fig 1): using experimental data, using both temperature conduction process and non-stationary thermal conduction. Thermal conduction, temperature conduction and thermal capacitance are general properties for temperature prediction methods. Usually building materials have thermal characteristics for normal environment, which can not exactly describe material properties at high temperatures. But many calculation methods lack accurate thermal characteristics describing building material properties at high temperatures. This article is intended for the analysis of this question.Article in Lithuanian.First Published Online: 30 Jul 2012